Stabilization of Grignard reagents by a pillar[5]arene host – Schlenk equilibria and Grignard reactions. Issue 9 (7th January 2020) - Shen, Lingyi; Zhao, Yanxia; Dai, Dihua; Yang, Ying-Wei; Wu, Biao; Yang, Xiao-Juan
Abstract : Grignard reagents with linear alkyl chains are encapsulated and stabilized by pillar[5]arene while preserving their reactivity in Grignard reactions. Abstract : Grignard reagents (RMgX) are widely used in organic synthesis. However, these highly reactive compounds are supplied in inflammable solvents, which causes extra complexity in their transportation. Herein we report that Grignard reagents with linear alkyl chains can be entrapped and stabilized by the macrocyclic host pillar[5]arene while preserving their reactivity.